Six new epigean species of Caecidotea (Isopoda: Asellidae) distributed along the Trans-Mexican Volcanic Belt in Central Mexico - García-Vázquez, Leonardo; Pedraza-Lara, Carlos; Rodríguez-Almaraz, Gabino (Zootaxa, 2021)
Six new epigean freshwater species of the genus Caecidotea in Mexico are described. These species were collected in waterbodies located along the Trans-Mexican Volcanic Belt (TMVB) and the eastern slope of the country: Caecidotea buzwilsoni sp. nov., Caecidotea chicoensis sp. nov., Caecidotea alvarezi sp. nov., Caecidotea mintzita sp. nov., Caecidotea zacapuensis sp. nov., and one additional species Caecidotea villalobosi sp. nov. is described from the Papaloapan basin at the Atlantic Slope of Mexico. The taxonomic treatment for each species includes a detailed description, figures of characters of diagnostic importance and comments. We also provide an updated map of Caecidotea records in Mexico. This work substantially increases the number of epigean Caecidotea known to occur in Mexico to 11 species, a new total of 99 species described to North America.